Assessing Utility of Parks: A Study of Parks in Raipur, India - Kukil Sharma; Khushboo Sharma; Vivek Agnihotri (International Journal of Urban Design and Development, 2026)
With the rapid growth of urbanization in India, urban parks are taking center stage as vital recreational spaces and community gathering spots. As cities continue to densify and open spaces shrink, public parks increasingly serve as essential infrastructure that supports physical health, social interaction, and environmental well-being. In addition to offering leisure and recreation, urban parks contribute to urban resilience by improving microclimatic conditions and enhancing the overall quality of life. Numerous developed nations have recently acknowledged the vital role of multi-functional public parks in fostering sustainable city development. Conversely, many existing public parks in developing nations suffer neglect or underuse. This study aims to evaluate the usability of parks and examine the determinants affecting the utilization of public parks in Raipur, India. It is a rapidly growing mid-sized city, presenting an appropriate context to assess how urban parks function within evolving urban environments. Parks were chosen based on their location, size, and amenities offered to ensure a representative assessment of different typologies of public open spaces. A total of three parks were examined, and an empirical study was conducted to determine variations in physical occupancy rates. We employed the System for Observing Play and Recreation in Communities (SOPARC) at the chosen park sites to collect data on the number of users, physical activity levels, and estimated ages. Through systematic observation and comparative analysis, this paper emphasizes vital factors in designing excellent public spaces for urban environments and offers a framework for creating successful public space designs. The designs that can encourage inclusivity, active use, and long-term sustainability in rapidly urbanizing cities.
Keywords: Design; Environment; public park; urban planning; utility